Teratogenic Effects of Third-Generation Antiepileptic Drug, Pregabalin: An In vivo Study - Singh, Krishna P.; Gupta, Kiran (Current Drug Safety, 2018)
Background: In the recent past, many third-generation antiepileptic drugs (AEDs) including Pregabalin (PGB) were launched for the treatment of diverse forms of epilepsy with better efficacy and safety profile than first-and-second-generation AEDs, but their teratogenic safety has not been established so far. Objective: The present study has been undertaken to evaluate the reproductive and teratogenic potential (external and skeletal) of a novel and third generation AED, PGB in pregnant albino rats. Methods: In this study, pregnant subjects were exposed to clinically relevant doses (41, 82 and 123 mg) of PGB from gestation days 6-20, and sacrificed on GD-21, and their fetuses were collected and examined to identify the birth defects and skeletal anomalies. Results: This study revealed that prenatal exposure to PGB induced dose-dependent substantial fetal resorptions, litter size, fetal length and weight; and variety of minor external and internal malformations in fetuses predominant with limbs, tail, eyes, abdomen including hemorrhages, and poor skeletal ossification. Conclusion: Thus, PGB was found to be teratogenic in rats at equivalent therapeutic doses, hence precaution should be taken before prescribing PGB to pregnant women with epilepsy.
Keywords: rat